2022
DOI: 10.3390/polym14102037
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of DNC Solid Dispersion by a Mechanochemical Method with Glycyrrhizic Acid and Polyvinylpyrrolidone to Enhance Bioavailability and Activity

Abstract: To exploit aqueous-soluble formulation and improve the anticoccidial activity of 4,4′-dinitrocarbanilide (DNC, active component of nicarbazin), this paper prepared DNC/GA/PVP K30 solid dispersion (SD) with glycyrrhizic acid (GA) and polyvinylpyrrolidone (PVP) K30 by a mechanical ball milling method without using any organic solvent. Fourier transform infrared spectroscopy, X-ray diffraction, differential scanning calorimetry, and scanning electron microscopy were used for the solid state characterization. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…This study has employed methods like FT-IR, DSC, XRD, and SEM to investigate the molecule configurations and the intermolecular interactions in the RA-SSOS after ball-milling, as they were previously reported to increase the solubility, stability, and bioavailability of difficult-to-solve drugs. RA-SSOS was first subjected to FT-IR spectroscopy. The spectral analysis showed that hydrogen bonds were generated between RA and the SSOS after ball-milling, facilitating the dispersion and stabilization of RA in solid states.…”
Section: Resultsmentioning
confidence: 99%
“…This study has employed methods like FT-IR, DSC, XRD, and SEM to investigate the molecule configurations and the intermolecular interactions in the RA-SSOS after ball-milling, as they were previously reported to increase the solubility, stability, and bioavailability of difficult-to-solve drugs. RA-SSOS was first subjected to FT-IR spectroscopy. The spectral analysis showed that hydrogen bonds were generated between RA and the SSOS after ball-milling, facilitating the dispersion and stabilization of RA in solid states.…”
Section: Resultsmentioning
confidence: 99%
“…Glycyrrhizic acid and its disodium salt (disodium 30-hydroxy-11,30-dioxoolean-12-en-3β-yl 2-O-β-D-glucopyranuronosyl-β-D-glucopyranosiduronate; Na2GA, fig. 1) are also effective natural low molecular weight complexing agents with increased biodegradability and bioavailability [21][22][23]. Glycyrrhizic acid (GA) is a triterpene glycoside extracted from liquorice root and demonstrates antiviral, anti-inflammatory, and antitumor properties [23].…”
Section: Introductionmentioning
confidence: 99%